4x-3=5rtx+4

Simple and best practice solution for 4x-3=5rtx+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3=5rtx+4 equation:


Simplifying
4x + -3 = 5rtx + 4

Reorder the terms:
-3 + 4x = 5rtx + 4

Reorder the terms:
-3 + 4x = 4 + 5rtx

Solving
-3 + 4x = 4 + 5rtx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5rtx' to each side of the equation.
-3 + -5rtx + 4x = 4 + 5rtx + -5rtx

Combine like terms: 5rtx + -5rtx = 0
-3 + -5rtx + 4x = 4 + 0
-3 + -5rtx + 4x = 4

Add '3' to each side of the equation.
-3 + -5rtx + 3 + 4x = 4 + 3

Reorder the terms:
-3 + 3 + -5rtx + 4x = 4 + 3

Combine like terms: -3 + 3 = 0
0 + -5rtx + 4x = 4 + 3
-5rtx + 4x = 4 + 3

Combine like terms: 4 + 3 = 7
-5rtx + 4x = 7

Reorder the terms:
-7 + -5rtx + 4x = 7 + -7

Combine like terms: 7 + -7 = 0
-7 + -5rtx + 4x = 0

The solution to this equation could not be determined.

See similar equations:

| 8=x+3-2x | | 3x+6=3x+2 | | 16=5x-11 | | 3/4-(7/12)-2/9) | | ×/15-1/5=3/5 | | 7-5x=5-x-7x | | X/3-17=11 | | 6(n+3)=3(2n+6) | | 7-5x=5-7x-7x | | (2x^4)(3x^2)= | | 15-g=22-2g | | 8d-.3333(6-9d)=42 | | (2x-15)/3 | | 4(k+3)+7(4k-7)=-69 | | 6f^3m+15f^4a^2= | | h(t)=14+32t+-16t^2 | | 3m-4=2(m-2) | | 5/2*(3v-4)=30 | | X/3=20/21 | | -7=3v-3v | | 5x-18=7x+40 | | 4a+2ab+4b(a-1)= | | 7x-3=7x+1 | | 3(5+5n)=2+2n | | 18+41n=42+49n | | 1/6/1/3 | | 2/3(1/2)-(-3/2)(-2/3) | | -26-6r=-8(r+2) | | (2x^2+x-1)-(x^2-x+1)= | | 3+x-15=20-3x | | 4x+7=4x+10 | | ×/8-1/2=6 |

Equations solver categories